1979
DOI: 10.1021/es60152a002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the decomposition of N-chloroalanine in aqueous solution

Abstract: The kinetics and mechanism of the decomposition of Nchloroalanine (a rapidly formed chlorination product of the common amino acid, alanine) have been investigated. The decomposition products have been shown to be acetaldehyde, ammonia, carbon dioxide, and chloride ion or, depending on pH, pyruvic acid, ammonia, and chloride ion. The kinetics were studied by UV-visible spectrophotometry and by the DPD-FAS titrimetric technique. The reaction is first order in N-chloroalanine and independent of alanine concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 9 publications
5
40
0
Order By: Relevance
“…The N-X-Valine is formed in less than one second by mixing the amino acid and the hypohalite solutions (both with a pH value of approximately 9.5). The reaction was always followed at 255 nm, the wavelength at which N-C1-Valine presents the maximum of absorption, this value coincides with that of most of other N-C1-amino acids [7,8]. The absorption spectrum of the N-C1-Valine does not vary with the pH value of the solution (between 4-14).…”
Section: Methodsmentioning
confidence: 65%
“…The N-X-Valine is formed in less than one second by mixing the amino acid and the hypohalite solutions (both with a pH value of approximately 9.5). The reaction was always followed at 255 nm, the wavelength at which N-C1-Valine presents the maximum of absorption, this value coincides with that of most of other N-C1-amino acids [7,8]. The absorption spectrum of the N-C1-Valine does not vary with the pH value of the solution (between 4-14).…”
Section: Methodsmentioning
confidence: 65%
“…The following main points emerged. NCP and NCDEA are considerably longer lived compounds (3.3 days and 2.2 days, respectively, at 25°C at pH 7.0) than the N-chloroamino acid, N-chloroalanine (55 min), calculated from the data of Stanbro and Smith (19). The half-lives of all three compounds do not change from pH 3.5 to pH 9, but increase dramatically below pH 3.0. Early in our study we found when we followed the NCP concentration by continuously monitoring its absorbance maximum at 262 nm that we photodecomposed it in the sample chamber of the spectrophotometer.…”
Section: Stability Of Organic N-chloraminesmentioning
confidence: 82%
“…41 Systematic studies on the kinetics and mechanism of the decomposition of N-chlorinated amino acids postulate the formation of imines which undergo further reactions. 20,21,23,[44][45][46][47][48][49][50] Some of these investigations suggests that decarboxylation and the loss of chloride ion occurs via a concerted Grob fragmentation mechanism. [51][52][53] Earlier results on the decomposition kinetics are somewhat controversial.…”
Section: Introductionmentioning
confidence: 99%